Research implications of social network analysis on psychology from 2019 to 2021: a systematic review - Lidia Sandra; Timothy Dillan; Sabar Aritonang (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This paper aims to give a systematic review on how Social Network Analysis (SNA) Applied in the psychology field of study. Research questions are used to analyse the dataset of journal articles and conference papers collected from IEEE Xplore. 50 papers gathered after applying the advance search of “Social Network Analysis” AND "Psychology" OR "Behaviour prediction" OR "Emotion prediction" OR "Depression" OR "Self-harm" OR "Happiness" ranging from the year 2019 to 2021. Of the 50 journals and papers collected, one journal is the most cited, namely the journal Armstrong R, Hall BJ, Doyle J, and Waters E in 2011. "Cochrane Update. 'Scoping the scope' of a Cochrane Review". The Journal of Public Health. We found that the discussion and uses of SNA in psychology can be divided as to propose a model of early prediction, to propose a model on how to handle and process the data, also analysing psychological factors and problems using the SNA and social computing itself.